Informality, Recurseo, and Entrepreneurship among Peruvians in Paterson, New Jersey, 1960–2001. - Muschi, Gianncarlo (Journal of American Ethnic History)
This article demonstrates how Peruvians in Paterson, New Jersey, have utilized entrepreneurship and informality to establish the first and most visible enclave of Peruvians in the United States since the 1960s. Central to this story is the concept of recurseo, a slang word used to describe the informal and creative means in which Peruvians utilize their labor experiences and kinship ties for self-employment. By using informality and recurseo, they were able to leave their factory jobs and establish their own businesses. These entrepreneurs opened restaurants, insurance offices, and small corporations that created an emergent market for products and services that contributed to the development of a thriving ethnic enclave. The informal economic practices introduced by Peruvians altered the social and economic landscape of Paterson and helped to revitalize the local economy. Through the use of oral histories from Peruvian entrepreneurs, archival material from local newspapers, and memoirs declassified by the Peruvian consulate of Paterson, this article challenges the oversimplified portrayal of Peruvians and other Latino immigrants as factory or farm workers with few opportunities for socio-economic advancement. It demonstrates that Latinos use informality and other alternative avenues to achieve wealth and ethnic empowerment in the process of adjustment and community building.